Pembentukan Kader Peduli Covid pada Masyarakat di Desa Rumbio, Kabupaten Kampar - Suyanto Suyanto; Zulkarnaini Zulkarnaini (Unri Conference Series: Community Engagement, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic has lasted almost two years. In Kampar Regency, there are a total of 3567 confirmed cases of COVID-19 as of May 1, 2021. One strategy that can be taken to reduce this Covid case is the development of cadres who care about Covid for village communities to recognize and report cases immediately to health facilities. For this reason, the Environmental Science Postgraduate Service Team of the University of Riau carried out community service activities in Rumbio village, Kampar district, Riau. This activity begins with the preparation of educational materials and is given to village cadres in order to increase their understanding of COVID-19. The method in implementing this service activity is carried out in 4 (four) stages, namely (1) Socialization, (2) Competency Improvement, (3) Implementation of activities, and (4) Monitoring and Evaluation. This activity is assisted by Kukerta students and periodic monitoring is carried out after the counseling. We also handed over visual media for Posbindu in the form of posters and banners. The existence of community service activities can improve the health status of the community.